SPE/DOE Symposium on Improved Oil Recovery 2004
DOI: 10.2118/89401-ms
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Partially Formed Polymer Gels for Application to Fractured Production Wells for Water-Shutoff Purposes

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractA laboratory study was conducted to characterize watershutoff polymer gels that are injected in the partially formed (partially matured) state into fractures (or other high permeability anomalies) that are in direct contact with production wells. Partially formed (<8-hr-old) 1X (0.5% polymer) chromium(III)-carboxylate/acrylamide-polymer (CC/AP) gels showed much lower (as much as 100 times less) effective viscosities (17 to 30 cp) during placement in a 1-mm-wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…More recently, it has been reported that certain relatively strong WSO gels impart RPM/DPR to fluid flow within gel-filled fractures. 45 However, because such relatively strong gels also significantly reduce the permeability to oil flow in fractures, these gels are better characterized as total shutoff gels than as RPM/DPR gels. DPR is only of value for water-shutoff treatments applied to production wells.…”
Section: Guidelines For Relative Permeability Modification Treatmentsmentioning
confidence: 99%
“…More recently, it has been reported that certain relatively strong WSO gels impart RPM/DPR to fluid flow within gel-filled fractures. 45 However, because such relatively strong gels also significantly reduce the permeability to oil flow in fractures, these gels are better characterized as total shutoff gels than as RPM/DPR gels. DPR is only of value for water-shutoff treatments applied to production wells.…”
Section: Guidelines For Relative Permeability Modification Treatmentsmentioning
confidence: 99%
“…Partially formed gels exhibit lower pressure gradients and may be able to penetrate into even tighter fractures. 34 Of course, gelants (i.e., gel formulations before reaching the gelation time) flow readily through virtually any open fracture and most porous media of moderate to high permeability. Incidentally, micro-fine cements have been used in place of more coarsely ground cements (e.g., Class H) to allow penetration into tighter voids and fractures.…”
Section: Yield Stressmentioning
confidence: 99%
“…Gels can be placed in fractures as gelants, 37 formed gels, 27,38 or partially formed gels. 34,35 Gelants (the fluid solution of crosslinker and polymer that exists before gelation) flow readily into fractures and medium to high permeability rock, exhibiting relatively low pressure gradients. However, gelants often experience problems with gravity segregation in fractures.…”
Section: Gelant/gel Properties During Placementmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that the total cost to separate, treat and dispose of this water is about USD 50 billion per year. Water can flow into wellbore as a result of either near wellbore problems or reservoir-related problems (Seright 2000;Sydansk 1990;Sydansk et al 2005). The mechanism that contributes to undesired water production needs be fully understood before appropriate measures can be taken.…”
Section: Introductionmentioning
confidence: 99%